Предмет: Алгебра,
автор: vikazavarina5
памагити решить, пожалуйстаа
Приложения:
vikazavarina5:
ага, а шо?
Ответы
Автор ответа:
1
1)
x^2 - y^2 - 6x + 9 = (x-3)^2 - y = (x - 3 - y) * (x - 3 + y)
2)
x^3 - 3x^2 - 4x + 12 = 0
x^2 * (x - 3) - 4 * (x - 3) = 0
(x - 3) * (x^2 - 4) = 0
(x - 3) * (x - 2) * (x + 2) = 0
Отсюда, x1 = -2 ; x2 = 2; x3 = 3
Похожие вопросы
Предмет: Русский язык,
автор: Чибанило
Предмет: Русский язык,
автор: RuzievaZarina
Предмет: Русский язык,
автор: 20461
Предмет: Қазақ тiлi,
автор: kirill7852
Предмет: Математика,
автор: kirilldenisov1